Chronic rhinosinusitis and its correlation with endoscopic anatomy of nose and paranasal sinuses: a cross-sectional study - Ghosh, Nachiketa; Das, Debabrata; Majumdar, Sayantani; Dey, Arijit; Haldar, Debdutta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic rhinosinusitis (CRS) is a common condition characterized by inflammation of nose and paranasal sinuses and is associated with significant morbidity and healthcare expenditure. The study was undertaken to evaluate the endoscopic findings in different cases of CRS and correlating those findings with the clinical features and severity of symptoms. Methods: A cross-sectional study was carried out at the outpatient Department of Otorhinolaryngology, R. G Kar Medical College and Hospital, Kolkata in a span of 18 months. A total of 56 patients who attended the outpatient department during the study period and met the inclusion criteria as well gave consent for participating in the study were taken as the sample size. The data was collected using history taking proforma. Results: Out of 56 patients, 51.8% were female, the most commonly affected age group was 31-40 years with 28.57% of patients. Majority of the patients 30.40% presented within one year of onset of symptoms, all the variables of clinical symptoms shows positive correlation statistically with the endoscopic findings, the most common anatomical variation was deviated nasal septum (DNS) present in 51.78% patients. Conclusions: A more extensive and detailed study needs to be done to determine conclusively whether the severity of symptoms can be used to predict the severity of disease in patients diagnosed as having chronic rhinosinusitis